New species of Caridina (Crustacea - Decapoda - Atyidae) from Vietnam - Thanh, Dang Ngoc; Tu, Do Van (Academia Journal of Biology, 2014)
The present paper deals with four new species of the genus Caridina (Atyidae): Caridina pseudoserrata sp.nov., collected from freshwaters mountain region Caobang (North Vietnam), Caridina rubropunctata sp. nov.- from Thainguyen (North Vietnam), Caridina vietriensis sp.nov. - from Phutho (North Vietnam) and Caridina uminensis sp.nov. - from wetlands U Minh Thuong (South Vietnam). The first and the second species are closely allied to the known species Caridina serrata Stimpson, the third - to Caridina tonkinensis Bouvier described from Tonkin (North Vietnam) and the last one - to Caridina cantonensis Yu - a chinese atyid. The diagnostic features of these four new species are given by the authors. 1. Caridina pseudoserrata sp.nov. (fig. 1, 2) Rostrum narrow, lanceolate in form, slightly curved downwards, reaching the middle of the 2nd segment of the antennular peduncle bearing 11-19 teeth on its dorsal border, 5-6 post orbital teeth and 1-2 teeth on the ventral. Peraeopod I with cheliped longer than carpus (1.6 times), the movable finger slightly equal or longer than palm (1.1). Carpus short, triangular in form, deeply excavated on the anterior border. Peraeopod II with cheliped a little longer than carpus (1.06), palm much shorter than finger. Endopod of the pleopod I of the male kidney-shaped, extending beyond the middle of the appendix masculina. Eggs dimensions: 1.05-1.2 ´ 0.7-0.75 mm. Remarks: this new species closely resembles Caridina serrata Stimpson and was formerly erroneously identified as its nominal subspecies Caridina serrata serrata Stimpson (Dang Ngoc Thanh, 1975). A recent taxonomical revision on this species in Vietnam showed that it is a different species, conforming to the opinion of Cai Y. and Ng, K. N (1999). in their revision in the Caridina serrata, principally in the following features: 1) Rostrum long, reaching the middle of the second segment of antennule. 2) Peraeopod I with movable finger equal or slightly longer than palm. 3) Endopod of male pleopod I with appendix interna, not overreaching beyond its extremity. 4) Pleopod II of the male with long appendix interna, extending beyond the middle of appendix masculina. 5) Big eggs, dimensions: 1.05-1.2 ´ 0.7-0.75 mm. 2. Caridina rubropunctata sp.nov. (fig. 3, 4) Body with characteristic red dots existing evenly in fixation status. Rostrum lanceolate in form, overreaching the 2nd segment to the middle of the 3nd segment of the antennular peduncle, bearing 12-16 teeth on the dorsal border, 5-7 teeth on the carapace, 2-4 teeth on the ventral. Stylocerit very long, extending to the distal extremity of the 2nd segment of antennular peduncle. Peraeropod I with movable finger longer than palm (1.27 time), long/wide ratio of the cheliped 2.08, cheliped longer than carpus (1.5), deeply excavated. Peraeopod II with movable finger longer than palm (1.05) carpus long/wide ratio 4.06. slightly longer than cheliped. Endopod of pleopod I of the male pseudorectangular in form, excavated in outer border, extending to the middle of exopod. Pleopod II of the male with very long appendix interna nearly reaching the distal extremity of appendix masculina. 3. Caridina uminensis sp.nov. (fig. 5, 6) Rostrum narrow, short, slightly curved downwards, reaching the distal extremity of second segment of the antennular peduncle, armed with 12-18 teeth on the dorsal border, 3-4 post orbital, 2-5 teeth on the ventral. Peraeopod I and II are similar in carpus structure. Peraeopod I with cheliped longer than carpus (1.25 times), movable finger longer than palm (1.5). Peraeopod II with carpus longer than cheliped (1.15), finger longer than palm (1.5). Endopod of pleopod I of the male long, coniform, distally rounded, reaching to 1/3 exopod. Appendix interna totally reduced or being only trace. Appendix masculina on pleopod II of the male with long appendix interna reaching its distal extremity. Eggs dimensions: 0.7-0.8 ´ 0.45-0.5 mm. 4. Caridina vietriensis sp.nov. (fig. 7, 8) Rostrum extending a little beyond the extremity of the antennular peduncle, stout in lateral view. Dorsal border slightly curved downwards in basal portion but almost straight in the distal portion, bearing 13-26 teeth, 4-6 postorbital, 1-6 teeth in ventral border. Stylocerit shorter than segment 1 of the antennular peduncle. Endopod of pleopod I in the male long lamellar in shape, distally narrowed, outer border concave, appendix interna short, reaching or overreaching beyond the distal extremity of the endopod. Appendix masculina in the male rod-shaped, appendix interna not reaching the middle of the appendix masculine. Egg dimensions: 0.9-0.95 ´ 0.5-0.6 mm. Comparision: the new species Caridina vietriensis sp. nov is related to Chinese species Caridina cantonensis Yu, but distinctly differs from the later in the rostrum distally straight, the characteristic endopod of the 1st male pleopod and the different shape and structure of its appendix masculina and appendix interna.